PERAN GURU BIMBINGAN DAN KONSELING DALAM MENCEGAH PERILAKU BULLYING DI SEKOLAH - Hindasyah Suryadi (IKIP Siliwangi, 2026)
This study aims to analyze the role of Guidance and Counseling teachers in preventing bullying in schools through a literature review approach. The review was conducted using various scholarly sources published between 2015 and 2025, including journals, books, and relevant research reports. The findings indicate that Guidance and Counseling teachers play a strategic role in three main dimensions: preventive, curative, and collaborative. In the preventive aspect, Guidance and Counseling teachers help raise students’ awareness of the negative impacts of bullying through guidance services, counseling sessions, and character-strengthening programs. In the curative aspect, Guidance and Counseling teachers provide individual and group counseling services to assist both victims and perpetrators in their psychological recovery and behavioral change processes. Meanwhile, in the collaborative aspect, Guidance and Counseling teachers work together with subject teachers, homeroom teachers, principals, and parents to create a safe and inclusive school environment. The study concludes that the effectiveness of Guidance and Counseling teachers’ roles is strongly influenced by professional competence, school policy support, and the involvement of the entire school community. Therefore, Guidance and Counseling teachers serve as key agents of change in fostering a school culture free from violence and in promoting students’ positive character development.